2020
DOI: 10.3390/biomedicines8060146
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics-Containing Yogurt Ingestion and H. pylori Eradication Can Restore Fecal Faecalibacterium prausnitzii Dysbiosis in H. pylori-Infected Children

Abstract: This study investigated the compositional differences in fecal microbiota between children with and without H. pylori infection and tested whether probiotics-containing yogurt and bacterial eradication improve H. pylori-related dysbiosis. Ten H. pylori-infected children and 10 controls ingested probiotics-containing yogurt for 4 weeks. Ten-day triple therapy plus yogurt was given to the infected children on the 4th week. Fecal samples were collected at enrollment, after yogurt ingestion, and 4 weeks after succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A recent review underlined the major influence of H. pylori on the bacterial community composition of the entire gastrointestinal tract, which might result in a complex dysbiosis impairing not only the stomach but also especially the gut microbiome [ 13 ], proving that children with H. pylori infection have a lower amount of fecal Bifidobacterium spp and a decreased Bifidobacterium to E. coli ration in their feces as compared to H. pylori -negative children [ 90 ]. A more recent study performed on pediatric patients with H. pylori infection found a significant decrease of fecal F. prausnitzii , an essential bacterium that favors the decrease of gut inflammation triggered by H. pylori lipopolysaccharide [ 16 ]. The same study suggested that supplementation with B. lactis and L. acidophilus has a positive effect on F. prausnitzii growth.…”
Section: Antibiotics Versus Probiotics In Pediatric H Pylor...mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review underlined the major influence of H. pylori on the bacterial community composition of the entire gastrointestinal tract, which might result in a complex dysbiosis impairing not only the stomach but also especially the gut microbiome [ 13 ], proving that children with H. pylori infection have a lower amount of fecal Bifidobacterium spp and a decreased Bifidobacterium to E. coli ration in their feces as compared to H. pylori -negative children [ 90 ]. A more recent study performed on pediatric patients with H. pylori infection found a significant decrease of fecal F. prausnitzii , an essential bacterium that favors the decrease of gut inflammation triggered by H. pylori lipopolysaccharide [ 16 ]. The same study suggested that supplementation with B. lactis and L. acidophilus has a positive effect on F. prausnitzii growth.…”
Section: Antibiotics Versus Probiotics In Pediatric H Pylor...mentioning
confidence: 99%
“…children with H. pylori infection → fecal F. prausnitzii → ↓ gut inflammation triggered by H. pylori lipopolysaccharide [ 16 ].…”
Section: Antibiotics Versus Probiotics In Pediatric H Pylor...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed that yogurt has positive effects on human health, reducing the risk of disease [3,4]. In fact, it has been observed that yogurt consumption helps treat diseases including obesity, allergies, intestinal tract inflammation, colon cancer, cardiovascular disease, and Helicobacter pylori infection [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…Although many studies have explored the positive factors registered by the consumption of yogurt in relation to the health and well-being of children and adolescents [5][6][7][8][9][10], little is known about their tastes in relation to these products and the factors influence their choices in purchasing functional foods, particularly yogurt.…”
Section: Introductionmentioning
confidence: 99%